Investigating the role of gamification in learning with virtual reality - Souropetsis, Markos; Kyza, Eleni A. (My University, 2024)
This study analyzed an inquiry-based VR activity in the context of a virtual visit to a cultural heritage site to understand how learning is affected by gamification elements in a virtual reality learning environment. An experimental research design was adopted to analyze the experience of 47 undergraduate students, of whom 24 used the gamified version of the inquiry-based VR learning environment while the remaining 23 used the same inquiry-based VR learning environment without the gamified elements. In our quantitative analyses we found that students in the gamified condition had statistically significant greater learning gains, higher perceived competence, and higher experienced immersion as compared to students in the non-gamified condition. In this report we present the results from the qualitative analysis of a case study consisting of two students, one from each condition seeking to understand how the gamification elements used in the VR environment may have contributed to these results. Data were collected using post-activity interviews. Our findings contribute empirical evidence on the effect of gamification in virtual reality settings and its positive relation to the learning process, perceived competence, and experienced immersion.
Keywords: Virtual Reality; Learning; Gamification; Cultural Heritage